2013
DOI: 10.1001/jamainternmed.2013.2352
|View full text |Cite
|
Sign up to set email alerts
|

High Variation Between Hospitals in Vena Cava Filter Use for Venous Thromboembolism

Abstract: Background:The extent to which vena cava filter (VCF) use varies between hospitals in the management of acute venous thromboembolism (VTE) is not clear.Methods : We conducted a retrospective observational study that compared the frequency of VCF use among California hospitals from January 1, 2006, through December 31, 2010. Using administrative hospital discharge data, we followed explicit criteria to identify nontrauma patients with acute VTE, and determined the frequency of VCF placement in each of the hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 26 publications
2
58
0
Order By: Relevance
“…Given the continued growth in VCF use and the variation that has been observed between institutions,13, 14, 15, 16, 17 assessment of what factors drive retrieval rates and timing of anticoagulation on a national scale is needed to evaluate clinical practice 18. This study sought to evaluate the trend in retrieval rates and patient factors associated with retrieval as well as the association between retrieval and anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Given the continued growth in VCF use and the variation that has been observed between institutions,13, 14, 15, 16, 17 assessment of what factors drive retrieval rates and timing of anticoagulation on a national scale is needed to evaluate clinical practice 18. This study sought to evaluate the trend in retrieval rates and patient factors associated with retrieval as well as the association between retrieval and anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of demonstrated benefit, cancer patients hospitalized with acute VTE are almost two times more likely to have a IVCF placed in comparison to non-cancer patients [10]. The clinical variables most strongly associated with IVCF placement in cancer patients were active bleeding, undergoing a major operation, presence of metastatic disease, greater severity-of-illness at the time of admission, and presence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of IVCF use in California hospitals [10], White et al observed wide variation in the use of IVCFs, from 0% to 39%, among patients admitted to a wide spectrum of hospitals with a principal diagnosis of VTE, even after adjusting for important clinical covariates. These findings suggest that patients with similar clinical characteristics are being treated or not treated with an IVCF based largely on local prevalent practice pattern.…”
Section: Thrombosis Research J O U R N a L H O M E P A G E : W W W mentioning
confidence: 99%
See 2 more Smart Citations